Evaluation of life quality of patients with chronic hepatitis C. - Schevchenko-Makarenko, O. P.; Schostakovych-Korets`ka, L. R.; Chykarenko, Z. O.; Tkachenko, V. D.; Lisnicha, O. O. (Medicni Perspektivi, 2017)
The article presents the adaptation data of the quality of life questionnaire (QOL) in patients with chronic viral hepatitis C (CVHC). Ball score of QOL of patients with CVHC was 5.09±1.04, 2nd group (with co-infection with HIV / HCV) - 4.60±1.13, control group - 5.92±0.52 (p<0.05)). The results of the analysis show that co-infection HIV / HCV is a serious problem for patients and significantly affects QOL. The use of the QOL questionnaire for chronic liver disease is a sensitive tool for measuring QOL in patients with CVHC and co-infection HIV / HCV. This informative and economical method can be implemented to assess the patient’s health both at the group and individual levels in patients with chronic liver disease in the population ofUkraine.